RESOLUTION OF TENSIONS IN THE ETHICAL DOCTRINE OF MAX SCHELER - Wilder, Alfred (Journal of Dharma, 1979)
It is widely appreciated that one of the more effective ways of introducing people to a particular area in philosophical thought is to confront them with certain relevant opinions which are opposed to .each other and at the same time appear to be well-founded. Although Max Scheler does not pursue this philosophical method with anything like the explicitness with which it is employed, for instance, in the dialectics of Hegel or te videtur quod non and sed contra systems of St. Thomas, it is clear, nonetheless, that in his work certain opposed tendencies continually engage one's attention. In general, Scheler's method is not to seek a resolution of these opppositions, as in the case of Hegel and St. Thomas, by some sort of synthesis or by apposite distinction. Rather, at least in his ethics, be tends simply to reject one direction of thought in favour of a contrary tendency. Scheler is perceptive and honest enough in his ethics not to reduce every initial tension by a simple rejection of the weight of the data which lies behind one of the opposed directions. Nonetheless. this method of resolution, whether it be employed in a simple or more nuanced manner, seems to be most congenial to his way of thought